2002
DOI: 10.3136/fstr.8.193
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Applications of Maillard-Type Protein-Polysaccharide Conjugates.

Abstract: This review summarizes the properties of Maillard-type protein-polysaccharide conjugates through naturally occurring reaction in a dry state from the viewpoint of the development of new industrial proteins. Maillard-type protein-polysaccharide conjugates showed excellent emulsifying properties superior to conventional commercial emulsifiers, heat stability, and antimicrobial activity. Therefore, the conjugates can be useful for industrial applications as natural emulsifiers, antimicrobial agents devoid of toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
153
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(156 citation statements)
references
References 26 publications
3
153
0
Order By: Relevance
“…Thus the Maillard reaction leads to the formation of different chemical species and promotes changes in antioxidant properties that are positively correlated with the development of browning (Manzocco et al, 2001;Kato, 2002;Miller and Gerrard, 2005). The MRPs of WPI conjugated to rare sugars show enhanced binding of free radicals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the Maillard reaction leads to the formation of different chemical species and promotes changes in antioxidant properties that are positively correlated with the development of browning (Manzocco et al, 2001;Kato, 2002;Miller and Gerrard, 2005). The MRPs of WPI conjugated to rare sugars show enhanced binding of free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Maillard reaction products (MRPs) are formed following heat processing of food and the reaction products have some beneficial effect on food quality. The current trend is to use MRPs as commercial food additives in applications as emulsifiers, antioxidants and antibacterial agents (Ames, 1992;Volkin et al, 1995, van Boekel, 1998Cloos and Christgau, 2002;Kato, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…[4] The techno-functional characteristics of proteins can be intensified using physical, chemical, or enzymatic treatments to obtain food ingredients for different applications. [5] One modification recognized as being suitable for producing speciality ingredients for food applications is proteinpolysaccharide conjugation via a Maillard-type reaction. In order to obtain better functions, we previously conjugated MBPI with glucose to increase its solubility, emulsification activity, and emulsification stability.…”
Section: Introductionmentioning
confidence: 99%
“…It was thus demonstrated that i) protein-dextran conjugates obtained with high MW dextran are more effective for improving the emulsifying properties of protein source (Wong, Day, & Augustin, 2011) and ii) increasing MW of dextran slows down the rate of glycation through MR (Jiménez-Castaño, Villamiel, & López-Fandiño, 2007;Spotti et al, 2013). For this latter reason, MR with dextran is performed in dry conditions in order to ensure low water activity (Kato, 2002).…”
Section: Emulsifying and Antioxidant Properties Of A Shrimp (Pandalusmentioning
confidence: 99%